1971
DOI: 10.1093/oxfordjournals.aje.a121307
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Canine Respiratory Viruses. I. Experimental Infection of Dogs With an Sv5-Like Canine Parainfluenza Agent1

Abstract: and J. S. Reif. Studies of canine respiratory viruses. I. Experimental infection of dogs with an SV5-like canine parainfluenza agent. Amer J Epidem 94: 147-165, 1971.-A parainfluenza virus which was recovered from a case of kennel cough at the University of Pennsylvania kennels was found capable of infecting all dogs without pre-existing antibodies on introduction into the nasopharynx, as proven by virus recovery, for 5 to 9 days after inoculation and by rises in specific antibodies. The infection was readily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…The virus was renamed parainfluenza virus 5 (PIV5) by the ITCV in 2009. It is believed that PIV5 contributes to kennel cough in dogs (15)(16)(17)(18)(19). Even though infection of dogs with PIV5 did not lead to kennel cough (20,21), kennel cough vaccines containing live-attenuated PIV5 have been used on dogs for more than 30 years without raising any safety concerns for dogs or humans.…”
mentioning
confidence: 99%
“…The virus was renamed parainfluenza virus 5 (PIV5) by the ITCV in 2009. It is believed that PIV5 contributes to kennel cough in dogs (15)(16)(17)(18)(19). Even though infection of dogs with PIV5 did not lead to kennel cough (20,21), kennel cough vaccines containing live-attenuated PIV5 have been used on dogs for more than 30 years without raising any safety concerns for dogs or humans.…”
mentioning
confidence: 99%
“…The significance of mumps virus findings should be interpreted cautiously, particularly in view of SV-5 antibodies in guinea pig serum commonly used as a source of complement in complement-fixation procedures [4]. A cross-reaction between mumps virus and SV-5 hyperimmune serum has been demonstrated [41]. J u d g q by the data presented in that study, it is possible that the mumps virus-related encephalitic syndrome described by these authors was, in reality, caused by canine parainfluenza virus.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first isolation of a canine parainfluenza virus from a dog with a respiratory disease [5], canine parainfluenza viruses in dogs have been manifested as infections restricted to the respiratory tract [2]. Clinical signs vary from a dry cough [2] to pneumonia [41]. Mortality rates are low.…”
mentioning
confidence: 99%
“…Subsequent studies revealed that the virus was frequent in dogs with respiratory disease [11,22,42,110,137,158], suggesting a key role, along with Bordetella bronchiseptica, in the aetiology of ITB.…”
Section: Canine Parainfluenzavirusmentioning
confidence: 99%
“…Small amounts of virus can be recovered from the local lymph nodes, but not from other lymphatic tissues. In naturally infected dogs, simultaneous infections with other viral and bacterial agents are quite common and clinical signs may be more severe [2,22,137].…”
Section: Canine Parainfluenzavirusmentioning
confidence: 99%